Effect of Different Metal Promoters on Ni-Based Catalyst for CO2 Reforming and Partial Oxidation of Methane to Syngas - Liu, Yuanfeng; Zhou, Liang; Hou, Zhenshan; Eli, Wumanjiang (Asian Journal of Chemistry, 2013)
The combining CO2 reforming and partial oxidation of methane to syngas over modified Ni catalysts has been researched. A series of alkali metal and alkaline earth metal-modified Ni catalysts have been prepared by co-impregnation. The catalytic activity of these catalysts was evaluated by conducting the combining CO2 reforming and partial oxidation of methane in a fixed-bed reactor. Results of the investigation suggested that alkaline earth metal-modified Ni catalysts exhibited an excellent catalytic activity and stability in comparison with with alkali metal-modified Ni catalysts in the combined reaction processes. The order of catalytic activity among these catalysts was 12Ni-2Ca/Al2O3 > 12Ni-2Ba/Al2O3 > 12Ni-2Mg/Al2O3 > 12Ni-2Na/Al2O3 > 12Ni-2K/Al2O3.